"And have you done anything so far?" An examination of lay treatment of children's symptoms. Issue 6600 (19th September 1987) - Cunningham-Burley, S; Irvine, S
Abstract : Interview data and health diary material were collected for an investigation of mothers' perceptions of their children's illnesses and of how they routinely coped with minor ailments in their children. The descriptions offered by the mothers of how they treated their children's symptoms and their actual use of various remedies as reported in the health diaries helped clarify the issues and processes concerned in their use of proprietary medicines and home remedies and their attitudes towards prescriptions. There was extensive use of proprietary medicines, yet mothers also used some home remedies or took no action at all. They were found to treat their children's symptoms themselves, contacting their general practitioner only if symptoms did not clear up or became more serious. Generally mothers should be treated as competent in caring for a child whose health and behaviour are causing concern, and in these cases the skills of the general practitioner should be viewed as complementing those of the mother. Mothers do not invariably expect a prescription from the doctor.